Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A=x^4+6x^3+7x^2–6x+1=x^4+(6x^3–2x^2)+(9x^2–6x+1)
= x^4+2x^2(3x–1)+(3x–1)^2 =(x^2+3x–1)^2
chỉnh lại tí
Đặt P(x)=x4+6x3+7x2- 6x+1
Đặt y=x2-1
=>y2=x4-2x2+1
P(x)=x4-2x2+1+6x3-6x+9x2
=(x2-1)2+6x(x2-1)+9x2
Q(y)=y2+6xy+9x2
=(y+3x)2
P(x)=(x2-1+3x)2
\(x^3+6x^2+11x+6=\left(x+1\right)\left(x+2\right)\left(x+3\right)\)
\(^{=x^3-3x^2+5x^2-15x+9x-27}\)
\(=x^2\left(x-3\right)+5x\left(x-3\right)+9\left(x-3\right)\)
\(=\left(x-3\right)\left(x^2+5x+9\right)\)
\(x^3+2x^2-6x-27\)
\(=x^3+5x^2+9x-3x^2-15x-27\)
\(=x\left(x^2+5x+9\right)-3\left(x^2+5x+9\right)\)
\(=\left(x-3\right)\left(x^2+5x+9\right)\)
ts cld b lv ag
\(x^3+6x^2-13x-42\)
\(x^3+6x^2-13x-42\)
\(=\left(x+7\right)\left(x-3\right)\left(x+2\right)\)
b, \(2x^3-x^2+3x+6\)
\(=2x^3+2x^2-3x^2-3x+6x+6\)
\(=2x^2\left(x+1\right)-3x\left(x+1\right)+6\left(x+1\right)\)
\(=\left(x+1\right)\left(2x^2-3x+6\right)\)
6x3 - 11x2 - x - 2
= 6x3 - 12x2 + x2 - 2x + x - 2
= ( 6x3 - 12x2 ) + ( x2 - 2x ) + ( x - 2 )
= 6x2( x - 2 ) + x( x - 2 ) + 1( x - 2 )
= ( x - 2 )( 6x2 + x + 1 )